2015
DOI: 10.1111/inm.12159
|View full text |Cite
|
Sign up to set email alerts
|

Raiders of the Lost Art: A review of published evaluations of inpatient mental health care experiences emanating from the United Kingdom, Portugal, Canada, Switzerland, Germany and Australia

Abstract: Forming interpersonal therapeutic relationships with mental health Service Users remains a key aspect of the practice of Psychiatric/Mental Health nurses. Given the omnipresence of the concept within the relevant literature the reader could be forgiven for asking: why would Psychiatric/Mental Health nurses opine about something so basic, so ubiquitous and so central to the theory and practice of our discipline? While the authors could locate no substantive argument that refutes the role or value of such relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
43
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 54 publications
3
43
0
Order By: Relevance
“…They reported that the TR was fundamental to their clinical practice, but that daily activity regarding the TR was not included in the protocols and clinical pathways, and consequently, it was not always a priority in their daily work (Pazargadi, Fereidooni Moghadam, Fallahi Khoshknab, Alijani Renani, & Molazem, ). This finding is in agreement with that of Cutcliffe, Santos, Kozel, Taylor, and Lees (), who noted that there was increasing evidence that the importance and value of the TR were not recognised in clinical practice.…”
Section: Discussionsupporting
confidence: 92%
“…They reported that the TR was fundamental to their clinical practice, but that daily activity regarding the TR was not included in the protocols and clinical pathways, and consequently, it was not always a priority in their daily work (Pazargadi, Fereidooni Moghadam, Fallahi Khoshknab, Alijani Renani, & Molazem, ). This finding is in agreement with that of Cutcliffe, Santos, Kozel, Taylor, and Lees (), who noted that there was increasing evidence that the importance and value of the TR were not recognised in clinical practice.…”
Section: Discussionsupporting
confidence: 92%
“…While patients experience a lack of high‐quality interaction with and meaningful activities involving staff, staff describe being hindered to work in line with their ideals due to a lack of structure and the need to manage chaos (Cleary ; Cutcliffe et al . ; Goulter et al . ; Graneheim et al .…”
Section: Introductionmentioning
confidence: 99%
“…They also deliver care for those people experiencing an acute exacerbation of their illness, which may involve challenging behaviours that may pose a risk to safety (Mullen 2009). In light of this, the model of care can too easily revert to custodial approaches that rely on observation and monitoring rather than engagement and interaction, because the admission is seen as a strategy in and of itself (Bertram & Stickley 2005;Cutliffe et al 2015;Mullen 2009). With this custodial approach, interventions have tended to be dominated by medication, while psychosocial interventions are often underutilized, despite an established evidence base (Crowe & Porter 2014;O'Brien & Cole 2004).…”
Section: Introductionmentioning
confidence: 99%